THE EFFECT OF CAPITAL ADEQUACY, LIQUIDITY AND CREDIT RISK ON PROFITABILITY (Study of National Commercial Banks Listed on the Indonesian Stock Exchange for the 2018-2022 Period) - Putu Feby Febriana Artadhi; I Gde Kajeng Baskara (Adisam Publisher, 2024)
Based on Law of the Republic of Indonesia Number 10 of 1998 concerning Banking, banks are business entities that collect funds from the public in the form of savings and distribute them to the public in the form of credit and/or other forms in order to improve the standard of living of many people. The bank's performance in maintaining its stability can be seen from the bank's ability to gain profits so that what is used is profitability. This research aims to test and analyze the influence of capital adequacy, liquidity and credit risk on profitability. This research is quantitative research in associative form, which was conducted at national commercial banks listed on the Indonesia Stock Exchange for the 2018-2022 period. The sample determination method in this research is a non-probability sampling technique with a purposive sampling method. The number of samples obtained was 27 banks with 135 observation data. Multiple linear analysis is used to test the effect of capital adequacy, liquidity and credit risk on profitability. The results of this research indicate that capital adequacy has an insignificant negative effect on profitability. Liquidity does not have a significant effect on profitability. Credit risk has a significant negative effect on profitability. The theoretical implications of this research can provide additional information and empirical evidence related to theory and can strengthen the results of previous research regarding capital adequacy, liquidity and credit risk on profitability. The practical implications of this research are able to contribute to the management of national commercial banks in the form of risk management study material and considerations for customers.